Pro Tools 7 power! - Colin MacQueen (Thomson Course Technology, 2006)
Get the most out of Pro Tools with the definitive guidebook! Covering the LE, M-Powered, and HD versions of Pro Tools for music, post, and multimedia users at all levels, Pro Tools 7 Power!, Second Edition is the perfect resource for both newcomers looking to get up and running, and more advanced users who would like a complete desk reference on the new version. Completely updated for Pro Tools 7.4, everything from basic audio concepts and setting up your system to editing, mixing, plug-ins, MIDI, and much more is here in a usable format that explains techniques in plain language. Helpful keyboard shortcuts for Windows and Macintosh as well as informative notes and helpful tips are included throughout the text. The companion CD-ROM includes more than 60 minutes of interactive movie tutorials from Cool School Interactus" that help reinforce what you've learned